A holistic approach to participatory crop improvement in wheat - Virk, Daljit S.; Harris, D.; Raghuwanshi, B.S.; Raj, A.G.B; Sodhi, P.S.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
The term "participatory crop improvement" is used to cover all aspects of crop improvement where farmers are involved in a participatory role. In this paper, we describe the approach and results for participatory crop improvement in wheat, in Luna Wada sub district, Gujarat, India. Nine villages were selected for study, and within each village, farmers were ranked into categories by wealth. An initial baseline survey on farming practices was conducted by semi structured interviews on a sample of farmers. Selected farmers from each wealth category kelp weekly farm calendars of all operations in their wheal fields. Selected fields were termed "intensive data plots." They provided a basis for analyzing Ihe farming system and profitability by wealth category, as well as for identifying constrains. The baseline surveys revealed that upper-category farmers benefitted most from the sale of wheat produce. The lower-category farmers consumed a large part of their produce. Intensive data plots showed that upper-category farmers accrued higher net gains from wheat cultivation than Ihe lower-category farmers. Participatory varietal selection (PVS) offered new varieties to farmers for selection. PVS resulted in significant replacement of the old variety Lok 1, grown in about 90% of the area, by many varieties that increased yield levels and on-farm biodiversity. Resource-poor farmers benefitted as much as the better-off farmers from PVS activities. Participating farmers experimented on a simple, cheap agronomic intervention: seed priming. Most farmers intended to adopt it because of its multiple beneficial effects, including increased yields. This holistic approach to participatory methods was effective in analyzing poverty issues, identifying constraints and new opportunities, and monitoring impact.